La persistencia mítica de Cantuña: un ensayo interpretativo a través de los estudios del imaginario (Crítica) - Fabara Espín, Jorge Gonzalo (2023)
The construction of the Church of San Francisco in Quito, Ecuador (1534/1535-1680), has acquired a mythical dimension in local imaginaries, especially highlighted by one of the most well-known and repeated legends in the country: that of the Indigenous Cantuña and his pact with the devil. This paper seeks its origins, theorizes on the importance of mythical elements in the collective imaginary and its narrative within the social fabric, and explores different conceptions used in imaginary studies for its approach. To this end, it first approaches bioanthropological definitions to interpret universal archetypal images (Durand); furthermore, it seeks the structural analysis of this foundational legend and the persistence of certain elements over time, as well as their relationships and interactions (Lacan). Finally, this work proposes a possible understanding of the myth and its persistence as a product of violence and guilt (Girard) with respect to the colonial process.